Ecosystem services of native and introduced bamboo species in the Huasteca Potosina, Mexico: uses of bamboo - Cruz-Armendáriz, Natalia María; Ruiz-Sanchez, Eduardo; Reyes-Agüero, Juan Antonio (Instituto de Ecología, A.C., 2023)
Background and Aims: There are seven native bamboo species in the Huasteca Potosina (HP), but the richness of introduced species is unknown. For both groups there is no record of the ecosystem services (ES) they provide. Therefore, the objectives of the study were to record the presence of introduced bamboo species in the HP and to identify the ES of native and introduced species. Methods: Botanical explorations were carried out to visit all the municipalities of the study area; 57 botanical collections were made. In order to know the ES of native and introduced species, observations were made in the field, especially in localities where bamboo is grown and used, and we interviewed 31 key informants. Key results: In addition to the seven native bamboo species in the HP there are 11 introduced taxa (ten species and one variety), all of which are woody culms. Eight species and one variety are native to Asia, one to South America, and one introduced from the state of Veracruz, Mexico. The most widely distributed introduced species are Bambusa vulgaris, B. vulgaris var. vittata and B. oldhamii. The main use of woody bamboo is for construction and the native species most used for this is Guadua velutina. The introduced species are produced for decoration, living fence and construction. Conclusions: In the HP there are 44 ha of commercial bamboo plantations, together with the native species they provide three ES and five uses. The results of this work are the basis for future research on the ES of bamboo in the HP. It is necessary to continue monitoring commercial plantations, since they are increasing; in addition to evaluating the effects of different management practices in plantations and potential uses, especially of native species.